2016
DOI: 10.1155/2016/5984709
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory, Phase II Controlled Trial of Shiunko Ointment Local Application Twice a Day for 4 Weeks in Ethiopian Patients with Localized Cutaneous Leishmaniasis

Abstract: The clinical efficacy and safety of Shiunko ointment (phase II clinical trial) was investigated in 40 Ethiopian patients with cutaneous leishmaniasis. Patients were randomized to receive treatment with Shiunko ointment or placebo (n = 20, each), applied on the lesion twice a day for 4 weeks. Clinicoparasitological assessments were performed before treatment, weekly for 4 weeks, and then 4, 8, and 12 weeks after the end of treatment. A marked reduction in lesion size was observed on week 16 of treatment in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…Mechanism studies revealed that Shiunko promoted the epithelization, angiogenesis, and granulation tissue formation of wounds ( Huang et al, 2004 ; Lu et al, 2008 ; Chak et al, 2013 ). Recently, clinical trials proved that Shiunko might be also effective for radiation-induced dermatitis in patients with breast cancer and localized cutaneous leishmaniasis ( Na-Bangchang et al, 2016 ; Kim et al, 2021 ). NF3, a two-botanical drug formulation comprised Astragali radix and Rehmanniae radix, is another one which has been extensively investigated for the treatment of diabetic foot ulcer ( Lau et al, 2008 ; Lau et al, 2009a ; Zhang et al, 2011 ; Lau et al, 2012 ).…”
Section: Multiherbal Preparations With Wound Healing Propertiesmentioning
confidence: 99%
“…Mechanism studies revealed that Shiunko promoted the epithelization, angiogenesis, and granulation tissue formation of wounds ( Huang et al, 2004 ; Lu et al, 2008 ; Chak et al, 2013 ). Recently, clinical trials proved that Shiunko might be also effective for radiation-induced dermatitis in patients with breast cancer and localized cutaneous leishmaniasis ( Na-Bangchang et al, 2016 ; Kim et al, 2021 ). NF3, a two-botanical drug formulation comprised Astragali radix and Rehmanniae radix, is another one which has been extensively investigated for the treatment of diabetic foot ulcer ( Lau et al, 2008 ; Lau et al, 2009a ; Zhang et al, 2011 ; Lau et al, 2012 ).…”
Section: Multiherbal Preparations With Wound Healing Propertiesmentioning
confidence: 99%
“…Three small clinical trials have been done so far. The only placebo-controlled trial was done on LCL patients using a Chinese medical ointment called Shiunko [96], which was not better than placebo, with cure rates of 20% (4/20) and 25% (5/20) respectively. Two small clinical trials were done over 20 years ago, using rifampicine with amithiozone versus pentamidine (LCL only) [97] and itraconazole versus placebo (10 LCL and 4 DCL) [98], of which only all six patients treated with pentamidine and two treated with placebo clinically improved.…”
Section: Treatmentmentioning
confidence: 99%
“…A total of 808 study subjects participated in the 22 studies [ 8 11 , 13 18 , 25 36 ]. Twelve studies (nine case series [ 8 , 9 , 25 27 , 29 , 30 , 32 , 33 ] and three case reports [ 10 , 11 , 35 ]) documented treatment outcomes as part of routine clinical practice.…”
Section: Resultsmentioning
confidence: 99%